The Effectiveness of Using Short Drama for Students in Writing Narrative Text - Mesida Laia; Jenita Anjani Br Sembiring; Junita Siahaan (Universitas Pahlawan Tuanku Tambusai, 2026)
Writing is an essential skill in English learning; however, many students still face difficulties in developing idea and organizing narrative texts effectively. This study aimed to determine the effectiveness of using short dramas for students in writing narrative text at SMP swasta Santo Yoseph Medan. Short drama was selected as the treatment because it provides contextual and visual representations of narrative elements that can help students generate ideas and organize narrative texts more effectively. A quasi-experimental design was employed involving 60 eighth-grade students divided into an experimental group and a control group. Data were collected through pre-test and post-test writing assessments and analyzed using and independent samples t-test. The finding revealed that the experimental group achieved a higher post-test mean score (75.38) than the control group (55.73). Statistical analysis showed a significant difference between the groups (Sig.=0.0000.05;t=10.487). Furthermore, content and organization were the writing aspects that improved the most. It can be concluded that short drama is effective in improving student’s narrative writing skills.